2022
DOI: 10.20452/pamw.16302
|View full text |Cite
|
Sign up to set email alerts
|

The cardiometabolic predictive value of anthropometric parameters, vascular ultrasound indexes and fat depots among patients with high cardiovascular risk: an 8-year prospective cohort study

Abstract: The cardiometabolic predictive value of anthropometric parameters, vascular ultrasound indexes and fat depots among patients with high cardiovascular risk: an 8year prospective cohort study

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Currently, the study of adipose tissue such as visceral, body surface, and pericardial adipose tissue is attracting increasing attention and has been detected to be associated with the development of numerous diseases ( 1 , 2 ). A prospective study showed that preperitoneal fat thickness or body surface area was related to the development of insulin resistance and diabetes ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the study of adipose tissue such as visceral, body surface, and pericardial adipose tissue is attracting increasing attention and has been detected to be associated with the development of numerous diseases ( 1 , 2 ). A prospective study showed that preperitoneal fat thickness or body surface area was related to the development of insulin resistance and diabetes ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the study of adipose tissue such as visceral, body surface, and pericardial adipose tissue is attracting increasing attention and has been detected to be associated with the development of numerous diseases ( 1 , 2 ). A prospective study showed that preperitoneal fat thickness or body surface area was related to the development of insulin resistance and diabetes ( 1 ). Ishikawa et al ( 2 ) demonstrated a significant correlation between epicardial adipose tissue volume and overall longitudinal strain of the left ventricle assessed using speckle echocardiography in patients with preserved left ventricular ejection fraction and no left ventricular regional ventricular wall motion abnormalities.…”
Section: Introductionmentioning
confidence: 99%